Identification of ABC Transporter Interaction of a Novel Cyanoquinoline Radiotracer and Implications for Tumour Imaging by Positron Emission Tomography. - Rozanna L Slade; Federica Pisaneschi; Quang-De Nguyen; Graham Smith; Laurence Carroll; Alice Beckley; Maciej A Kaliszczak; Eric O Aboagye (PLoS ONE)
Background The epidermal growth factor receptor (EGFR) is overexpressed in many cancers including lung, ovarian, breast, head and neck and brain. Mutation of this receptor has been shown to play a crucial role in the response of non-small cell lung carcinoma (NSCLC) to EGFR-targeted therapies. It is envisaged that imaging of EGFR using positron emission tomography (PET) could aid in selection of patients for treatment with novel inhibitors. We recognised multi-drug resistant phenotype as a threat to development of successful imaging agents. In this report, we describe discovery of a novel cyanoquinoline radiotracer that lacks ABC transporter activity. Methods Cellular retention of the prototype cyanoquinoline [18F](2E)-N-{4-[(3-chloro-4-fluorophenyl)amino]-3-cyano-7-ethoxyquinolin-6-yl}-4-({[1-(2-fluoroethyl)-1H-1,2,3-triazol-4-yl]methyl}amino)-but-2-enamide ([18F]FED6) and [18F](2E)-N-{4-[(3-chloro-4-fluorophenyl)amino]-3-cyano-7-ethoxyquinolin-6-yl}-4-[({1-[(2R,5S)-3-fluoro-4,5-dihydroxy-6-(hydroxymethyl)oxan-2-yl]-1H-1,2,3-triazol-4-yl}methyl)amino]but-2-enamide ([18F]FED20) were evaluated to establish potential for imaging specificity. The substrate specificity of a number of cyanoquinolines towards ABC transporters was investigated in cell lines proficient or deficient in ABCB1 or ABCG2. Results FED6 demonstrated substrate specificity for both ABCG2 and ABCB1, a property that was not observed for all cyanoquinolines tested, suggesting scope for designing novel probes. ABC transporter activity was confirmed by attenuating the activity of transporters with drug inhibitors or siRNA. We synthesized a more hydrophilic compound [18F]FED20 to overcome ABC transporter activity. FED20 lacked substrate specificity for both ABCB1 and ABCG2, and maintained a strong affinity for EGFR. Furthermore, FED20 showed higher inhibitory affinity for active mutant EGFR versus wild-type or resistant mutant EGFR; this property resulted in higher [18F]FED20 cellular retention in active mutant EGFR expressing NSCLC. Conclusion [18F]FED20 binds EGFR but is devoid of ABC transporter activity, thus, has potential for EGFR imaging.